2016
DOI: 10.1039/c6ra03798d
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed synthesis of quinoline derivatives via tandem Knoevenagel condensation, amination and cyclization

Abstract: A novel regioselective synthesis of 2-aminoquinolines and 2-arylquinoline-3-carbonitriles is described via copper-mediated tandem reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The supramolecular assembly of compound (V) was not mentioned in the original report (Dhiman et al, 2016) and we therefore discuss it here. Four hydrogen bonds are present (Table 3) and these together link the molecules into very complex sheets, whose formation can, however, be readily analysed in terms of two simpler one-dimensional substructures (Ferguson et al, 1998a,b;Gregson et al, 2000).…”
Section: Figurementioning
confidence: 97%
See 2 more Smart Citations
“…The supramolecular assembly of compound (V) was not mentioned in the original report (Dhiman et al, 2016) and we therefore discuss it here. Four hydrogen bonds are present (Table 3) and these together link the molecules into very complex sheets, whose formation can, however, be readily analysed in terms of two simpler one-dimensional substructures (Ferguson et al, 1998a,b;Gregson et al, 2000).…”
Section: Figurementioning
confidence: 97%
“…As noted above, the structure of compound (V) has recently been reported at ambient temperature and refined in the space group P1 with Z 0 = 2 (Dhiman et al, 2016). Comparison of the atomic coordinates for corresponding pairs of atoms in this structure showed that the two molecules in the selected asymmetric unit are very precisely related by a noncrystallographic 2 1 screw axis along (x, 3 4 , 3 4 ), and a detailed examination of this structure for additional symmetry elements (PLATON; Spek, 2009) found a 100% fit to space group P2 1 /n with Z 0 = 1, in a unit cell with dimensions a = 10.896 Å , b = 8.952 Å , c = 13.292 Å and = 96.15 , very similar to the monoclinic unit cell found here at 100 K. Although a request to the authors of the original report for a copy of their .hkl file proved fruitless, we are nonetheless reasonably confident that compound (V) does not, in fact, exhibit temperature-dependent polymorphism, but that the ambient-temperature structure was refined in the wrong space group.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Kumar's group developed a method to prepare 2‐aminoquinolines 86 through CuI‐catalyzed tandem reaction of bromobenzaldehydes 84 , cyanoacetates 85 , and NaN 3 (Scheme 16). [ 50 ] This strategy showed wide substrate scope, excellent tolerance toward functional group, and used readily available compounds as the starting materials, but high reaction temperature was needed. The yields of 86a with and without the ligand were respectively obtained in 62% and 20%, which suggested that the ligand advanced the conversion of 87 to 88 , and 88 to 89 .…”
Section: L‐proline‐assisted Copper‐catalyzed Cascade Reactionsmentioning
confidence: 99%
“…In continuation of our ongoing efforts towards developing newer methodologies for the synthesis of N ‐fused heterocycles,,, herein, we wish to report an efficient and operationally simple synthetic method for the construction of 3‐aryl‐γ‐carbolines via Cu‐catalyzed one‐pot, multicomponent reaction of 2‐bromo‐1‐methyl‐1 H ‐indole‐3‐carbaldehydes with terminal alkynes and aqueous ammonia.…”
Section: Introductionmentioning
confidence: 99%